Optimization of Time in Classroom Listening Comprehension Tasks - Sánchez, María Jesús; Fernández-Sánchez, Alfredo (Miscelánea: A Journal of English and American Studies, 2016)
The purpose of this research was to verify the appropriate number of times (1, 2 or 3) that EFL students (B2.1 level) should listen to oral texts for an appropriate comprehension. In addition, we sought to find whether listening comprehension is affected by the type of exercise that participants are asked to respond to: whether a multiple-choice or fill-in-the-blanks option. The research was done with a Pretest/Posttest design and 51 participants. Intra-group comparisons confirmed that there is no significant difference at this level, indicating an equal performance regardless of the treatment (once, twice, or 3 times). This study makes a practical contribution to the teaching field since it establishes the number of times that students at this level should listen to the oral text (once). It was also found that multiple choice option exercises may be more suitable for an assessment of comprehension, an idea that is consistent with the literature which points to recognition exercises (multiple-choice) as being easier than those in which retrieval is involved (fill-in-the-blanks).